Glioblastoma multiforme - case presentation and literature review - Jakub Litak; Joanna Litak; Wojciech Czyżewski; Paulina Miziak (Kazimierz Wielki University, 2019)
Glioblastoma multiforme is a most common primary brain tumor with extreme malignancy index. Presented case of 75y.o. patient diagnosed with GBM underwent full treatment : surgery and adjuvant proton-therapy. Despite new therapy development, overall survival time of GBM patients is still unacceptable.